Association between Stress, Depression and Anxiety with Body Fat Percentage among Medical Students of Faculty of Medicine and Health Sciences of Atma Jaya Catholic University - Dewi, Sheilla; Tenggara, Riki; Hasan, Surilena (Public Health and Preventive Medicine Archive, 2021)
Background and purpose: Medical students have higher rate of stress, depression and anxiety compared to the general population of the same age and are at risk of having high level of body fat percentage. The objective of this study is to determine the association between stress, depression and anxiety with body fat percentage among medical students. Methods: This is a cross sectional study carried out among 90 undergraduate medical students of Faculty of Medicine and Health Sciences of Atma Jaya Catholic University, North Jakarta, from January to March 2019. Sampling was performed by using the stratified proportional random sampling method. Stress, depression and anxiety were measured with Depression Anxiety Stress Scale 42 and body fat percentage was measured with Bioelectrical Impedance Analysis. Data analysis was performed by using Spearman correlation. Results: Based on sociodemographic characteristics, the respondents were mostly 19 years old, female and 1st year students. This study shows that 34.4% of respondents had stress, 22.2% had depression and 48.9% had anxiety. This study shows that 62.1% of the male respondents and 32.8% of the female respondents had high body fat percentage. Spearman analysis showed moderate positive correlation between stress (r=0.505), depression (r=0,403) and anxiety (r=0,485) with body fat percentage among the respondents. Conclusion: There is a significant association between stress, depression and anxiety with body fat percentage among medical students. This study intends to be an input for educational institutions to screen for mental health problems (stress, depression and anxiety) as well as body fat percentage in students that may affect their well-being and learning process so that they can be diagnosed and intervened as early as possible.